The Complexity of Enzymic Control of Hydrogen Peroxide Concentration May Affect the Regeneration Potential of Plant Protoplasts. - De Marco, A. (1996)
Total peroxidase, NADH-peroxidase, ascorbate peroxidase, superoxide dismutase, and catalase activities were measured in tobacco (Nicotiana tabacum) leaves and in regenerating and nonregenerating protoplasts isolated from the same tissue and cultured for 2 weeks. The specific ranges of H2O2 concentration at which the enzymes scavenging the active forms of oxygen may efficiently operate and the activities of those enzymes were determined in an extract from tobacco leaves and in dividing and nondividing tobacco mesophyll protoplasts. The overall H2O2-scavenging enzyme activities were similar in both protoplast populations during the 2 to 3 d of culture. After 3 d, the regenerating protoplasts started to divide and both the antioxidant enzyme activities and the total peroxidase activity increased; in contrast, the viability and the H2O2-scavenging enzyme activities in nonregenerating protoplasts dramatically decreased. Surprisingly, the regenerative potentiality in dividing protoplasts was specifically correlated with a higher NADH-peroxidase activity, which resulted in a net H2O2 accumulation in the cells. Light, which causes the accumulation of active forms of oxygen in photosynthetic organelles, also stimulated catalase and ascorbate peroxidase activities in dividing protoplasts. We suggest that the localization of H2O2 rather than its absolute concentration might be responsible for oxidative stress and that controlled amounts of H2O2 are necessary to allow proper cell-wall reconstitution and the consequent cell division.